Making Good Use of Adaptive Management - Doremus, Holly; Andreen, William L.; Camacho, Alejandro E.; Farber, Daniel A.; Glicksman, Robert L.; Goble, Dale D.; Karkkainen, Bradley C.; Rohlf, Dan; Tarlock, A. Dan; Zellmer, Sandra B.; Jones, Shana Campbell; Huang, Yee (Center for Progressive Reform, 2011)

Essentials of Utilization-Focused Evaluation - Patton, Michael Quinn (SAGE Publications, 2011)
Based on Michael Quinn Patton's best-selling Utilization-Focused Evaluation, this briefer book provides an overall framework and essential checklist steps for designing and conducting evaluations that actually get used. The new material and innovative graphics present the utilization-focused evaluation process as a complex adaptive system, incorporating current understandings about systems thinking and complexity concepts. The book integrates theory and practice, is based on both research and professional experience, and offers new case examples and cartoons with Patton's signature humor.
Google-Books-ID: BaMgAQAAQBAJ
Keywords: Reference / Research; Research

Taking responsibility for complexity: how implementation can achieve results in the face of complex problems - Jones, Harry (ODI, 2011)
OCLC: 837825712